Association of swine vertnin (VRTN) gene with production traits in Duroc pigs improved using a closed nucleus breeding system. (2nd November 2012) - Hirose, Kensuke; Mikawa, Satoshi; Okumura, Naohiko; Noguchi, Go; Fukawa, Kazuo; Kanaya, Naoe; Mikawa, Ayumi; Arakawa, Aisaku; Ito, Tetsuya; Hayashi, Yoichi; Tachibana, Fumio; Awata, Takashi
Abstract: Vertnin ( VRTN ) is involved in the variation of vertebral number in pigs and it is located on Sus scrofa chromosome 7. Vertebral number is related to body size in pigs, and many reports have suggested presence of an association between body length (BL) and meat production traits. Therefore, we analyzed the relationship between the VRTN genotype and the production and body composition traits in purebred Duroc pigs. Intramuscular fat content (IMF) in the Longissimus muscle was significantly associated with the VRTN genotype. The mean IMF of individuals with the wild‐type genotype (Wt/Wt) (5.22%) was greater than that of individuals with the Wt/Q (4.99%) and Q/Q genotypes (4.79%). In addition, a best linear unbiased predictor of multiple traits animal model showed that the Wt allele had a positive effect on the IMF breeding value. No associations were observed between the VRTN genotype and other production traits. The VRTN genotype was related to BL. The Q/Q genotype individuals (100.0 cm) were longer than individuals with the Wt/Q (99.5 cm) and Wt/Wt genotypes (98.9 cm). These results suggest that in addition to the maintenance of an appropriate backfat thickness value, VRTN has the potential to act as a genetic marker of IMF.